Viral zoonoses and food of animal origin: a re-evaluation of possible hazards for human health - Kaaden, Oskar-Rüger; Czerny, Claus-Peter; Eichhorn, Werner (Springer, 1997)
The investigations of virus infections naturally transmitted from animals to men are a challenge to multidisciplinary science. Some of these zoonoses are very common, others are sporadic but show a life-threatening clinical course. The contributions presented by world-wide leading experts are going to update the present scientific, administrative and legislative knowledge in the field of food-borne virus infections in men. Major topics include classic zoonoses, pox, irido, influenza, enteric and newly emerging virus diseases and their role for Public Health including strategies to avoid virus transmission by biopharmaceutical products. The contributions are aimed at public and veterinary public health authorities, diagnostic and scientific institutes as well as food producing and pharmaceutical companies
Gesehen am 05.09.2024